Tapering strategies in elite British endurance runners - Spilsbury, K. L.; Fudge, B. W.; Ingham, S. A.; Faulkner, S. H.; Nimmo, M. A. (European Journal of Sport Science, 2015)
The aim of the study was to explore pre-competition training practices of elite endurance runners. Training details from elite British middle distance (MD; 800 m and 1500 m), long distance (LD; 3000 m steeplechase to 10,000 m) and marathon (MAR) runners were collected by survey for 7 days in a regular training (RT) phase and throughout a pre-competition taper. Taper duration was [median (interquartile range)] 6 (3) days in MD, 6 (1) days in LD and 14 (8) days in MAR runners. Continuous running volume was reduced to 70 (16)%, 71 (24)% and 53 (12)% of regular levels in MD, LD and MAR runners, respectively (P < 0.05). Interval running volume was reduced compared to regular training (MD; 53 (45)%, LD; 67 (23)%, MAR; 64 (34)%, P < 0.05). During tapering, the peak interval training intensity was above race speed in LD and MAR runners (112 (27)% and 114 (3)%, respectively, P < 0.05), but not different in MD (100 (2)%). Higher weekly continuous running volume and frequency in RT were associated with greater corresponding reductions during the taper (R = -0.70 and R = -0.63, respectively, both P < 0.05). Running intensity during RT was positively associated with taper running intensity (continuous intensity; R = 0.97 and interval intensity; R = 0.81, both P < 0.05). Algorithms were generated to predict and potentially prescribe taper content based on the RT of elite runners. In conclusion, training undertaken prior to the taper in elite endurance runners is predictive of the tapering strategy implemented before competition.